Budged Disclosure of Sorong Serah Aji Krame in Sasak Tribe Wedding - Maezura, Intan; Jumaidi, Lalu Takdir (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine the amount of budget to carry out the sorong serah aji krame tradition of Sasak wedding custom, as well as to show that the symbols used in this culture are unique in accounting. The interpretive paradigm and the phenomenological method were used in this research. Data collection methods include conducting literacy studies and interviews. Data analysis involves the stages of data collection, data reduction, data presentation, and conclusion. The results showed that the budget varies depending on the conditions that occur, the level of ownership (Aji 33, 66, 100), and whether the equipment is owned or rented. The value of religion-based local cultural values as an implementation of sorong serah aji krame accounting is symbolized by AMANAH accounting A(Charity), M(Deliberation), A(Custom), N(Normative), A(Accountability), and H(Harmony).